A Brief Discussion on Zheng He’s Nautical Charts - And the Presentation of the Ancient-Present Contrast of Zheng He’s Nautical Charts - Jianqiu, Zhu (The International Hydrographic Review, 2015)
Originally, Zheng He’s Nautical Charts were published in Wu Bei Zhi (a collection of military books, 1621), Vol. 240, compiled by Mao Yuanyi of the Ming Dynasty. The charts are thought to have been drawn in the early 15th century. For more than one hundred years, scholars worldwide have been doing research on Zheng He’s Nautical Charts and have published many books and theses. On the basis of these previous works, the author has continued to investigate the charts from the angle of marine cartography, written several papers, and compiled the Ancient-Present Contrast of Zheng He’s Nautical Charts (which were exhibited at the XIHth International Hydrographic Conference) as a chief editor. This paper describes the features of Zheng He’s Nautical Charts briefly and introduces the newly-compiled Ancient-Present Contrast of Zheng He’s Nautical Charts.